Holistic Work Engagement pada Tenaga Kesehatan di Kota Jakarta Barat: Pengaruh Digital Quotient, Authentic Leadership, dan Perceived Organizational Support selama Covid-19 - Adellia Anggun Trisnawati; Kerin Sianto; Lady Aldli Seansyah; Nopriadi Saputra (Jurnal Akuntansi, Keuangan, dan Manajemen, 2021)
Purpose: This study aimed to determine the impact of digital quotient, authentic leadership, and perceived organizational support on work engagement of employees who work in the health industry during this COVID-19 in West Jakarta. Research methodology: The methods in this research were quantitative and survey. We obtained primary data through the questionnaire distribution with 391 respondents of health care workers who work in West Jakarta. This study used multiple regression techniques as the data analysis technique. Results: The study results indicate that digital quotient, authentic leadership, and perceived organizational support influence work engagement. Limitations: Only digital quotient, authentic leadership, perceived organizational support, work engagement variables, and health care workers in West Jakarta were assessed in this research. Contribution: This study shows the level of work engagement, digital quotient, authentic leadership, perceived organizational support and how digital quotient, authentic leadership, and perceived organizational support affect work engagement. Employers or organizations can use this research to improve their employees' work engagement by noticing their employee's level of digital quotient and implementing authentic leadership and perceived organizational support.